Recurrent pregnancy loss: a shared stressor: couple-orientated psychological research findings - Scharli, Pauline; Schick, Maren; Langer, Laila; Ainsworth, Asrin; Ditzen, Beate; Strowitzki, Thomas; Wischmann, Tewes; Kuon, Ruben-Jeremias (Fertility and sterility, 2020)
Objective - To compare the psychological impact of recurrent pregnancy loss (RPL) on affected men and women and to determine risk and protective factors in both partners. - Design - Cross-sectional study. - Setting - University-affiliated fertility center. - Patient(s) - Ninety female/male couples and 14 women. - Intervention(s) - Participants completed a questionnaire covering psychological risk factors (ScreenIVF), experience of pregnancy losses, coping strategies, and partnership satisfaction. - Main Outcome Measure(s) - Comparison of psychological risk factors, perception of RPL, and coping strategies between both partners and analysis of the influence of risk and protective factors. - Result(s) - In the ScreenIVF, 47.7% of women versus 19.1% of men showed a risk for anxiety, 51.7% versus 19.1% a risk for depression, and 28.1% versus 30.7% a risk for limited social support. The use of avoiding coping styles seems to be less favorable with regard to the psychological risk than active strategies. Having a child together and a satisfying partnership correlated with a lower risk for depression. Sharing the experience of RPL with others and being in a satisfying relationship correlated with a higher social support. - Conclusion(s) - Both men and women affected by RPL show high risks for developing depression and anxiety, underlining the importance of also including the male partners. The factors of communication with others, a satisfying relationship, and already having a child together correlate with decreased psychological risks. We advocate for health care professionals to implement screening for anxiety, depression, and social support for both partners and support them in dealing with RPL. - Registration Number - The study is registered in the German Clinical Trials Register (DRKS), number DRKS00014965. - Pérdida recurrente del embarazo: un factor de estrés compartido: resultados de la investigación psicológica orientada a la pareja. - Objetivo - Comparar el impacto psicológico de la pérdida recurrente del embarazo (RPL) en hombres y mujeres afectados y determinar los factores de riesgo y protección en ambos integrantes de la pareja. - Diseño - Estudio transversal. - Entorno - Centro de fertilidad afiliado a la universidad. - Paciente (s) - Noventa parejas mujer/hombre y 14 mujeres. - Intervención (es) - Los participantes completaron un cuestionario que cubría los factores de riesgo psicológico (ScreenIVF), experiencia de las pérdidas del embarazo, estrategias de afrontamiento y satisfacción de la pareja - Principales medidas de resultado - comparación de factores de riesgo psicológico, percepción de RPL y estrategias de afrontamiento entre ambos integrantes de la pareja y análisis de la influencia de los factores de riesgo y protección. - Resultado (s) - En el ScreenIVF, el 47,7% de las mujeres vs. el 19,1% de los varones presentaron riesgo de ansiedad, 51,7% vs. 19,1% riesgo de depresión y 28,1% vs. 30,7% riesgo de apoyo social limitado. El uso de estilos de afrontamiento de evitación parece ser menos favorable con respecto al riesgo psicológico que las estrategias activas. Tener un hijo juntos y una relación satisfactoria se correlacionó con un menor riesgo de depresión. Compartir la experiencia de RPL con otros y tener una relación satisfactoria se correlacionó con un mayor apoyo social. - Conclusión (es) - Tanto los hombres como las mujeres afectados por RPL muestran un alto riesgo de desarrollar depresión y ansiedad, lo que subraya la importancia de incluir también a la parte masculina de la pareja. Los factores de comunicación con los demás, una relación satisfactoria y tener un hijo juntos se correlacionan con la disminución de los riesgos psicológicos. Abogamos por que los profesionales de la salud implementen exámenes de detección de ansiedad, depresión y apoyo social para ambos integrantes de la pareja y los apoyamos para lidiar con la RPL.
Gesehen am 14.02.2022